Pengaruh Promosi, Citra Merek, Dan Kualitas Produk Terhadap Loyalitas Pelanggan Pada Konsumen Somethinc di Kota Bekasi - Nadhira Nur Iklimah; Indra Muis (Indo Publishing, 2026)
years. Amid fierce competition, local skincare brand Somethinc experienced a significant market share decline, dropping from the top position in 2022 to fifth place in the fourth quarter of 2024. This highlights the importance of understanding factors influencing customer loyalty. This study analyzes the effects of promotion, brand image, and product quality on Somethinc customer loyalty in Bekasi City, partially and simultaneously. A quantitative approach was used with purposive sampling involving 102 Somethinc consumers in Bekasi City. Data was collected via a Likert scale questionnaire and analyzed using multiple linear regression with SPSS version 29.0. Results show promotion has a positive and significant effect on customer loyalty (t = 3.148; sig. = 0.002), brand image has a positive and significant effect (t = 2.394; sig. = 0.019), and product quality is the most dominant variable (t = 4.764; sig. < 0.001). Simultaneously, all three variables significantly influence customer loyalty (F = 45.487; sig. < 0.001), with a determination coefficient of 58.2%. It is concluded that promotion, brand image, and product quality collectively shape customer loyalty, with quality as the most decisive factor.